Hydroxytyrosol Ameliorates Intervertebral Disc Degeneration and Neuropathic Pain by Reducing Oxidative Stress and Inflammation. (2nd November 2022) - Yu, Haichao; Zhang, Zhen; Wei, Fahong; Hou, Guowei; You, Yonggang; Wang, Xiangyu; Cao, Shiqi; Yang, Xiaoqing; Liu, Weibo; Zhang, Shaofu; Hu, Fanqi; Zhang, Xuesong
Abstract : Low back pain (LBP) seriously affects human quality of life. Intervertebral disc degeneration (IVDD) is the main pathological factor that leads to LBP, but the pathological mechanism underlying IVDD has not been fully elucidated. Neuropathic pain caused by IVDD is an important pathological factor affecting people's daily lives. Therefore, it is very important to identify therapeutic drugs to ameliorate IVDD and secondary neuropathic pain. Hydroxytyrosol (HT) is a natural compound derived from olive leaves and oil and has anti-inflammatory, antioxidant, and antitumor activities and other properties. In this study, TNF- α -stimulated human nucleus pulposus cells (HNPCs) were used to simulate the local inflammatory microenvironment observed in IVDD in vitro to explore the role of HT in alleviating various pathological processes associated with IVDD. A rat needle puncture model was used to further explore the role of HT in alleviating IVDD. Lipopolysaccharide (LPS) was used to stimulate microglia in vitro to comprehensively explore the role of HT in alleviating neuropathic pain, and a rat model involving chronic compression of the dorsal root ganglion (CCD) was established to simulate the neuropathic pain caused by IVDD. This study suggests that HT reduces the expression of cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), the NOD-like receptor thermal protein domain associated protein 3 (NLRP3) inflammasome, a disintegrin and metalloproteinase with thrombospondin motifs-4 (ADAMTS-4) and matrix metalloproteinase-13 (MMP-13); inhibits the production of mitochondrial reactive oxygen species (ROS); and maintains mitochondrial homeostasis. Thus, HT appears to reduce the rate of apoptosis and mitigate the loss of major intervertebral disc components by inhibiting the nuclear factor kappa-B (NF- κ B) signaling pathway. Moreover, HT inhibited the secretion of COX-2, tumor necrosis factor- α (TNF- α ), interleukin (IL)-6, IL-1 β, and iNOS and activation of the NLRP3 inflammasome in microglia by inhibiting the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) and extracellular regulated protein kinase (ERK) signaling pathways. In conclusion, HT plays a protective role against IVDD and secondary neuropathic pain by inhibiting the NF- κ B, PI3K/AKT, and ERK signaling pathways.